Sound insulation of timber hollow box floors: Collection of laboratory measurement data and trend analysis. Issue 2 (June 2021) - Homb, Anders; Conta, Simone; Geyer, Christoph; Kumer, Niko
The industrialisation of timber buildings has improved strongly in recent years. When long span is required, timber hollow-box floor elements are increasingly used due to their structural performance. The aim of this paper is to assess the acoustic performance of timber hollow-box floors, determine the governing parameters and identify the corresponding trends. We collected results from laboratory measurements covering both airborne and impact sound insulation from four different laboratories covering a wide range of application. Data include the bare floor constructions and their combination with different floating floors including both lightweight solutions and hybrid solution. We performed the analysis focusing on following parameters: element stiffness, element mass per unit area, dynamic stiffness of the resilient layer, cavity filling and floating floor material. We present the collected data both frequency-dependent and as single number quantities. General trends and features are identified in the frequency-dependent diagrams. A further detailed analysis is based on the single number quantities. It includes a general relationship between element mass per unit area and given requirements for R'W + C50-5000 and L'n, w + CI, 50-2500 . Furthermore, diagrams are presented illustrating the dependence of impact sound insulation numbers on the cavity filling, the dynamic stiffness of the resilient layer and the type of material used for the floating floor. The additional mass in the cavity improves both airborne and impact sound insulation by minimum 10 dB. This, combined with a floating floor, allows the fulfilment of a wide range of requirements.